The Science, Technology, Engineering, Mathematics (STEM)-based Problem-Based Learning (PBL) Learning Model on the Numeracy Skills - Siska; Samsul Maarif (Universitas Pendidikan Ganesha, 2023)
The low numeracy ability of students is because the learning process carried out by the teacher is still centred on the use of the lecture method, so in the learning process, students tend to get bored quickly and find it difficult to understand the material presented by the teacher. This study aimed to identify the significant impact of the use of STEM-based PBL on students' numeracy skills in Grade V SD. This research belongs to the type of quantitative research using a quasi-experimental design with a nonequivalent control group design. The population in this study were all fifth-grade students, totalling 201 children. Sampling in the study was carried out using a purposive sampling technique, with the number of samples in this study, namely 25 students as the control group and 25 as the experimental group. Data collection in the study was carried out using the test method, with the research instrument being an essay test. The data obtained in the study were then analyzed through a prerequisite test, which consisted of the normality test, homogeneity test, hypothesis test using was T-test, and the effect size test. The results of the data analysis show that the application of STEM in PBL has a high effect on improving students' numeracy skills. Based on these results, applying the STEM-based PBL model significantly affects the numeracy abilities of fifth-grade students in elementary schools.